Probiotic interventions to reduce antepartum Group B streptococcus colonization: A systematic review and meta-analysis. (February 2022) - Hanson, Lisa; VandeVusse, Leona; Malloy, Emily; Garnier-Villarreal, Mauricio; Watson, Lauren; Fial, Alissa; Forgie, Marie; Nardini, Katrina; Safdar, Nasia
Highlights: Early onset Group B Streptococcus Disease prevention strategies vary between regions/countries. Numerous Lactobacilli species have antagonist activity against GBS in vivo. Based on the meta-analysis, antenatal probiotic interventions increased chance of negative GBS result by 79%. Probiotics are a primary prevention strategy that could reduce the need for intrapartum antibiotic prophylaxis (IAP). Midwives can lead and support the necessary larger well-controlled clinical trials. Abstract: Objective: To systematically review and meta-analyse studies of the efficacy of probiotics to reduce antenatal Group B Streptococcus (GBS) colonisation. Participants: Antenatal participants with known positive GBS colonisation or unknown GBS status. Intervention: Probiotic interventions containing species of Lactobacillus or Streptococcus . Design: Systematic review and meta-analysis. Measurements and findings: The systematic review included 10 studies. Five articles contained in vitro studies of probiotic interventions to determine antagonistic activity against GBS. Six clinical trials of probiotics to reduce antenatal GBS were systematically reviewed and meta-analysed. The meta-analysis revealed that the use of an antenatal probiotic decreased the probability of a positive GBS result by 44% ( OR  = 0.56, 95% CI = 8.7%, 194.1%, p  = 0.02) ( n  = 709). However, only one clinical trial of 10 had a low risk of bias. Key conclusions: The probiotic interventions subjected to in vitro testing showed antagonistic activity against GBS through the mechanisms of acidification, immune modulation, and adhesion. The findings of the meta-analysis of the clinical trials revealed that probiotics are a moderately effective intervention to reduce antenatal GBS colonisation. More well-controlled trials with diverse participants and with better elucidation of variables influencing GBS colonisation rates are needed. Implications for practice: Probiotic interventions appear to be a safe and effective primary prevention strategy for antenatal GBS colonisation. Application of this low-risk intervention needs more study but may reduce the need for intrapartum antibiotic prophylaxis in countries or regions where antenatal GBS screening is used. Midwives can be instrumental in conducting and supporting larger well-controlled clinical trials.